Penanganan Diversi Anak sebagai Tersangka dalam Tindak Pidana Pencurian Kenderaan Bermotor pada Polres Sibolga - Suprihanto Pardjanihadi; Ediwarman Ediwarman; Rizkan Zulyadi (Journal of Education, Humaniora and Social Sciences (JEHSS), 2021)
The research objective is to analyze the rule of law in the application of diversion to children; the factors causing the criminal act of theft of motorized vehicles by children and the diversion policy against child suspects in the crime of theft of motorized vehicles at the Sibolga Resort Police. The research method used is descriptive method, while the data analysis technique uses descriptive qualitative. The results of the study indicate that the rule of law in the application of diversion to children who commit criminal acts is regulated in Law No. 11 of 2012 concerning the Juvenile Criminal Justice System, namely in articles 6 – 15 and Law no. 35 of 2014 concerning Child Protection, namely article 1 number (2). Factors causing the theft are internal factors, namely economic factors where children come from families of weak economic groups, lack of parental supervision because they are busy at work, lack of legal awareness by children because they are still not mature in thinking, narcotics needs because they are wrong in the association of friends, external factors are the opportunity to commit theft, the influence of the environment where children are connected to criminal groups or motorcycle gangs, the influence of adults who try to take advantage of children to commit theft of motorized vehicles, and the number of collectors of stolen motorized vehicles. The diversion policy against child suspects in the crime of motor vehicle theft at the Sibolga Resort Police is carried out by means of formal and non-formal policies.